Liver fibrosis - Wallace, Karen; Burt, Alastair D; Wright, Matthew C (Biochemical journal, 2008)
Liver damage leads to an inflammatory response and to the activation and proliferation of mesenchymal cell populations within the liver which remodel the extracellular matrix as part of an orchestrated wound-healing response. Chronic damage results in a progressive accumulation of scarring proteins (fibrosis) that, with increasing severity, alters tissue structure and function, leading to cirrhosis and liver failure. Efforts to modulate the fibrogenesis process have focused on understanding the biology of the heterogeneous liver fibroblast populations. The fibroblasts are derived from sources within and out with the liver. Fibroblasts expressing alpha-smooth muscle actin (myofibroblasts) may be derived from the transdifferentiation of quiescent hepatic stellate cells. Other fibroblasts emerge from the portal tracts within the liver. At least a proportion of these cells in diseased liver originate from the bone marrow. In addition, fibrogenic fibroblasts may also be generated through liver epithelial (hepatocyte and biliary epithelial cell)-mesenchymal transition. Whatever their origin, it is clear that fibrogenic fibroblast activity is sensitive to (and may be active in) the cytokine and chemokine profiles of liver-resident leucocytes such as macrophages. They may also be a component driving the regeneration of tissue. Understanding the complex intercellular interactions regulating liver fibrogenesis is of increasing importance in view of predicted increases in chronic liver disease and the current paucity of effective therapies.